VIRTUAL SIMULATOR IN ONCOLOGY FOR TEACHING CATHETER CARE FULLY IMPLEMENTED FOR NURSING STUDENTS: EXPERIMENTAL STUDY. - das Graças Matsubara, Maria; Cijevschi, Eliza; Serpa, Leticia; Netto, Antônio; Saraiva, Daiane; Tarcia, Rita (RIIS: Revista de Investigação & Inovação em Saúde, 2025)
Background: the virtual simulator emerges as an effective technological tool in the teaching-learning process. Objective: to compare the effectiveness of two teaching strategies in training nursing students in oncology, focusing on catheter insertion and care for fully implanted central venous catheters. Methodology: an experimental, controlled, and randomized study conducted with 55 nursing students. Participants were divided into two groups - control and experimental - and underwent different educational interventions with identical content. Statistical analysis included hypothesis testing and regression, with a significance level set at 5%. Results: the sample included 55 students (mostly women, aged between 21 and 23). Both groups showed improvement in learning after the intervention, but without statistical significance. However, the experimental group showed a significant improvement (p=0.003) in managing fully central venous in relation to adverse events. No significant differences were observed concerning sociodemographic profile, education, or digital fluency. Conclusion: the training program using virtual reality simulation proved as effective as the face-to-face course combined with a virtual learning environment, with better outcomes in knowledge about adverse events for the experimental group.